NASI LEMAK PACKAGING: A CASE STUDY OF FOOD FRESHNESS AND DESIGN FLEXIBILITY - S., Maidin; A.N., Latiff (Journal of Advanced Manufacturing Technology (JAMT), 2015)
Nasi Lemak with various types of packaging, is one of the most popular cuisines in Malaysia and is popular nowadays with a take away concept. This project has redesign the current Nasi Lemak packaging due to the current design lacks of flexibility and could not keep the Nasi Lemak fresh longer. Comparative experiment of three types of Nasi Lemak packaging was conducted to determine the freshness level of Nasi Lemak to determine the best packaging. Results shows that typical Nasi Lemak packaging using banana leaf and paper stay fresh longer due to its packaging that enabled air to flow. This study has also developed three concepts of Nasi Lemak packaging based on survey with 30 final year UTeM undergraduate students. From the survey, it can be concluded that there are several criteria that should be addressed in the concept generation of a new Nasi Lemak packaging. This include, the packaging shoud fit fork and spoon, transparent, good size and should be easy to carry. The study also applied eco design concept into the Nasi Lemak packaging. The third concept was selected as the final new design of Nasi Lemak packaging because from the design perspective it is easy to be packed as well as it is convenient to user with the incorporation of a fork and spoon holder. In addition, its advantage from the perspective of environmental due to utilisation of eco-friendly material. For future study, it is recommended to have a more effective testing on the redesigned prototype Nasi Lemak packaging to determine the freshness level of Nasi Lemak.